Weed interference in sunflower. Competition in space - Fleck, Nilson Gilberto; Mengarda, Ildo Pedro; Pinto, Jesus Juares Oliveira (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were conducted in the Estação Experimental Agronômica of Universidade Federal do Rio Grande do Sul, in Guaíba, RS, Brazil, the first one during the growing season of 1984/85 and the second in 1985/86, to investigate the relationship between weed control in space and sunflower agronomic characteristics, examining the efficiency of weed control in certain interrows only. Eight treatments were compared, seven of which received mechanical control in 0%, 25%, 33%, 50%, 67%, 75% and 100% of the total number of interrows, whereas one treatment was submitted to hoeing in 100% of the plot area. The interference exerted by weeds not totally controlled in the space caused negative effects on sunflower agronomic characteristics. The crop presented a linear function to increasing in the area maintained weed-free during its cycle, showing positive increments in grain yield and, generally, also in the other agronomic characteristics evaluated, such as number of grains per head, grain weight, head diameter, and plant height.